Odpowiedzi

2010-03-17T15:52:46+01:00
A)5( X - 7)+2=-28
5x-35+2=-28
5x-33=-28
5x=-28+33
5x=-5|:5
x=1
b)5=4( x - 2)+9
5=4x-8+9
-4x=-1-5
-4x=-6|:(-4)
x=1.5
c) 2(x-1)+3(x+1)=26
2x-2+3x+3=26
5x=26+2-3
5x=25|:5
x=5
d) 4(3-x)+9=7(2+x)+29
12-4x+9=14+7x+29
-4x-7x=14+29-12-9
-11x=22|:(-11)
x=-2
d)2(x-3)+3(x-4)+4(x-5)=0
2x-6+3x-12+4x-20=0
9x=6+12+20
9x=38|:9
x=4,2(2)

8 3 8
2010-03-17T15:53:35+01:00
A. 5( X - 7)+2=-28
5x-35+2=-28
5x=-28+35-2
5x=5/ :5
x=1

B.5=4( x - 2)+9
5=4x-8+9
5+8-9=4x
4=4x/:4
x=1

C.2(x-1)+3(x+1)=26
2x-2+3x+3=26
5x=26+2-3
5x=25/:5
x=5

D.4(3-x)+9=7(2+x)+29
12-4x+9=14+7x+29
12+9-14-29=7x+4x
-22=11x/:11
x=-2

E.2(x-3)+3(x-4)+4(x-5)=0
2x-6+3x-12+4x-20=0
9x=38/:9
x=4²₉
4 3 4